Dye removal from aqueos solution by using adsorption on treated sugarcane bagasse - Saiful Azhar, Saad; Abdul Ghaniey Liew, Abdullah; Suhardy, Daud; Farizul Hafiz, Kasim; M.D Irfan Hatim (Science Publications, 2009)
Link to publisher's homepage at http://scipub.org/scipub/index.php